Integration of independent learning and physics innovation in STEAM-based renewable energy education to improve critical thinking skills in the era of Society 5.0 for Sustainable Development Goals (SDGs) 2030 - Indahwati Sri Dwi; Rachmadiarti Fida; Hariyono Eko; Prahani Binar Kurnia; Wibowo Firmanul Catur; Bunyamin Muhammad Abd Hadi; Satriawan Muhammad (E3S Web of Conferences, 2023)
This study aims to integrate Free Learning and Physics Innovation in STEAM-based Renewable Energy Education to improve critical thinking skills in Era Society 5.0 in order to achieve the 2030 Sustainable Development Goals (SDG). This research uses a literature review method that collects and analyzes related articles. The results showed that integrating Free Learning and Physics Innovation in STEAM-based Renewable Energy Education is an effective approach to improving students’ critical thinking skills. Renewable energy education is a relevant and important topic in SDG 2030, and the STEAM approach helps students understand and overcome this challenge. Era Society 5.0 emphasizes technology integration, so the educational approach must constantly be updated and adapted to the times. The results of this literature review can assist educators, policymakers, and researchers in developing educational strategies that align with the times’ needs.